Critical Review of Internationally Comparable Entrepreneurship Activity Measures - Crnogaj, Katja; Rebernik, Miroslav (Naše gospodarstvo/Our economy, 2013)
Many studies that place entrepreneurship in the centre of their research, especi- ally those exploring the influence of entrepreneurship on economic growth and development, often do not provide definitions and entrepreneurship measures that would be comprehensive enough for an in-depth empirical verification. Because measuring and internationally comparing entrepreneurship and its results are chal- lenging tasks, the entrepreneurship measures must be carefully chosen and interpre- ted so that they can be appropriately considered when preparing policy-making recommendations. In this paper, we more precisely define the entrepreneurship me- asures most often used at the national level and identify their strengths and weak- nesses as well as possible intersections.